Evaluating vision-specific quality of life and functional vision in a Brazilian population with Stargardt disease. Issue 2 (March 2023) - Gomes, Mirela L. S.; Mansur-Pantuzzo, Esther R.; Lagos, Angel A. R.; Corrêa, Humberto; Duarte, Dante; Frasson, Maria
Purpose: To compare the vision-specific quality of life (QoL) of individuals with Stargardt disease (STGD) with that of healthy individuals and to investigate the association between vision-specific QoL and functional vision. Methods: This cross-sectional study included 41 patients with STGD and 46 healthy volunteers matched by age and gender. Best corrected visual acuity (BCVA) was used to calculate the Functional Acuity Score (FAS) and Goldmann perimetry the Functional Field Score (FFS). These scores were combined to obtain the Functional Vision Score (FVS). Vision-specific QoL was assessed using the 25-item version of the National Eye Institute Visual Function Questionnaire (NEI VFQ-25). Results: The groups had similar sociodemographic and clinical characteristics. There were significant differences in BCVA, vision-specific QoL assessed by the NEI VFQ-25, and FVS ( p  < 0.001) between individuals with STGD and controls. The final total score and all the subscales of the NEI VQF-25 questionnaire were significantly lower in the STGD group ( p  < 0.001), except for the subscales general health, color vision, and ocular pain. NEI VFQ-25 results in the STGD group were positively correlated with family income, FVS, and FFS. FVS was the score best correlated with the NEI VFQ-25 total score. Conclusions: Individuals with STGD had significant impairment of vision-specific QoL and functional vision compared with controls and the FVS was the objective evaluation method most correlated with vision-specific QoL in this population.